The green hydrogen role in the global energy transformations - Sameer Algburi; Omer Al-Dulaimi; Hassan Falah Fakhruldeen; Doaa H. Khalaf; Raad Naser Hanoon; Feryal Ibrahim Jabbar; Qusay Hassan; Ali Khudhair Al-Jiboory; Stella Kiconco (Renewable and Sustainable Energy Transition, 2025)
Green hydrogen has the potential to significantly contribute to the global energy transition toward sustainable and decarbonized energy systems. Produced through renewable-powered electrolysis, green hydrogen provides a viable pathway for decarbonizing challenging sectors, such as heavy industry and transportation, while simultaneously addressing renewable intermittency by enabling large-scale energy storage and grid flexibility. This study evaluates the geopolitical and economic implications of developing robust green hydrogen supply chains, particularly in renewable resource-rich regions. Despite its promise, significant barriers persist, including high production costs, infrastructural inadequacies, and policy uncertainty. Emerging technological innovations, coupled with supportive financial strategies and comprehensive policy frameworks, can help overcome these barriers. The given outcomes recommended a strengthening international cooperation and implementing harmonized regulatory standards to accelerate green hydrogen adoption globally, positioning it as a core component of achieving net-zero emissions, driving economic growth, and advancing equitable energy transitions.